The islands of the sea (also including Aborigines, Maoris and Amerindians) - Tatford, Frederick Albert, 1901-; Echoes of Service (Bath, UK Echoes of Service, 1986)
Includes indexes, biographical details, maps, photographs, etc.
Brethren writer.
Keywords: Brethren movement -- missions -- Pacific Islands -- history; Brethren movement -- missions -- Australia -- history